BETWEEN TRADITION AND RHETORIC (BASED ON THE EXAMPLES OF POLISH 17TH- AND 18TH-CENTURY SECULAR SPEECHES) - Barłowska, Maria (Prace Polonistyczne, 2021)
The article examines the particular way in which authors of the 17th- and 18th- century Polish speeches (the examples of which have been taken from manuscripts and printed anthologies) referred to custom. This strategy was used not only to reinforce the argument by referring to the positively valued tradition, but it also served as a commentary on oratory rules and strategies. The recurrent references to custom that this article seeks to examine could be defined as causam actionis (analogously to causam scribendi) in which the act of speaking, the manner of speaking, and the content of the speech are justified by custom. The texts under discussion offer many remarks on decorum and expressing praise. They present detailed rules of conduct, e.g. a different set of rules applies to a speech delivered in the presence of the king or the queen.